2012
DOI: 10.1007/s10529-012-1011-7
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression and characterization of a novel salt-tolerant xylanase from Bacillus sp. SN5

Abstract: A xylanase gene (xyn10A) was cloned from Bacillus sp. SN5 and expressed in Escherichia coli. It encoded a 348-residue polypeptide of ~45 kDa. The deduced amino acid sequence had 68 % identity with the endo-1,4-beta-xylanase from Paenibacillus lactis 154 that belonged to family 10 of the glycoside hydrolases. Purified recombinant Xyn10A had maximum activity at 40 °C and pH 7.0, with the specific activity of 105 U/mg and a Km of 0.6 mg/ml for beechwood xylan. Xyn10A retained more than 80 % activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 14 publications
1
38
0
3
Order By: Relevance
“…The results showed differences from the other cold-adapted xylanases, such as xylanases from Bacillus sp. SN5 and G. mesophila KMM241 (Guo et al 2009;Bai et al 2012), which showed that Mg 2+ had no evident effect on activity. On the contrary, the activity of XynB from G. mesophila KMM241 was obviously inhibited by Mn 2+ (Guo et al 2009).…”
Section: Effects Of Metal Ions and Chemicals On Enzyme Activitymentioning
confidence: 97%
See 4 more Smart Citations
“…The results showed differences from the other cold-adapted xylanases, such as xylanases from Bacillus sp. SN5 and G. mesophila KMM241 (Guo et al 2009;Bai et al 2012), which showed that Mg 2+ had no evident effect on activity. On the contrary, the activity of XynB from G. mesophila KMM241 was obviously inhibited by Mn 2+ (Guo et al 2009).…”
Section: Effects Of Metal Ions and Chemicals On Enzyme Activitymentioning
confidence: 97%
“…The xylanases from Glaciecola mesophila (Guo et al 2009), Bacillus sp. SN5 (Bai et al 2012), Zunongwangia profunda (Liu et al 2014), and goat rumen contents belonging to the GH10 family showed obvious cold-adapted activity (Wang et al 2011). Additionally, several xylanases from G. mesophila KMM241 (Guo et al 2013), Pseudoalteromonas haloplanktis (Petegem et al 2003), and the environmental DNA library of lagoons (Lee et al 2006) belonging to the GH8 family also exhibited the cold activity.…”
Section: The Properties Of Xyn10a Effect Of Ph and Temperature On Actmentioning
confidence: 98%
See 3 more Smart Citations